ANALISIS MANAJEMEN PELAYANAN SEKOLAH INKLUSI MELALUI PENGAMATAN LINGKUNGAN FAKTOR INTERNAL DAN EKSTERNAL - Januariani (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2023)
Education is the right of every citizen, including Children with Special Needs (ABK). Education for ABK is carried out in the form of inclusive education. The achievement of goals in inclusive education is pursued in various ways, including through service management. Service management includes planning (planning), organizing (organizing), implementation (actuating), and supervision (controlling). This research is a type of qualitative research that aims to determine the analysis of inclusive school service management through environmental observations. Data collection techniques were carried out through in-depth interviews, observation, and documentation. While the data analysis technique is done by data exposure, data condensation, and drawing conclusions. The results of the study show that Muhammadiyah 1 Tulungagung Elementary School as a school providing inclusive services conducts a SWOT analysis when planning service programs for Students with Special Needs (PDBK). The results of the SWOT analysis are used to determine the type of service to be provided. Good service management is expected to be able to increase a sense of comfort, self-confidence, and the ability to socialize in students with special needs. Finally, the ultimate goal of inclusive education, namely increasing competency in PDBK, will be achieved.